Prediksi Emisi Metana Dari Limbah Domestik Dan Konversi Energi Listrik Di Surabaya Utara - I Made Satya Graha (Jurnal Ecocentrism, 2021)
Predictions for ten years of methane gas emissions in research are conducted on wastewater. To predict the emissions of methane gas ten years first calculated the level of methane gas emissions. Then made predictions to know the emissions of methane gas produced by domestic wastewater for the last ten years. This domestic wastewater from rusunawa. The calculation of methane gas emissions is carried out with reference to the method developed by IPCC 2006. Based on calculations, household wastewater generates methane gas emissions in 2007 of 5648.75 kgCH4 / year or 8610.91 m3 / year and continues to increase each year. The methane emission prediction result yields the equation y = 1538x2 + 5836x + 16610 to predict methane gas emissions over the next ten years. While the conversion of electrical energy in 2007 amounted to 770.90 kWh and increased every year along with the increase in methane gas emissions. The prediction result of electrical energy yields the equation y = 137,7x2 + 522x + 1487 to predict electric energy ten years ahead.